Comparison of hybrid and native corns with respect to physical quality, content of phenols and aflatoxins - Peña Betancourt, Silvia Denise; Carmona Medero, Miguel Ángel; Valladares Carranza, Benjamín (Revista Mexicana de Ciencias Agrícolas, 2018)
The concern for the quality and safety of the food consumed in Mexico has been increasing in recent times. Corn has a wide variety of genotypes, which in Mexico are consumed mainly as dough and tortillas. The aim of this study was to compare fifteen different genotypes of corns with respect to their physical quality, soluble phenolic content and af latoxin contamination. The commercial hybrid corn varieties analyzed were: panther, leopard, bear, 30T26, 30G40 from the state of Hidalgo; Cronos and DK2060 from the state of Morelos; Puma 1167, H516 and H519 from the State of Mexico; and five varieties native to Puebla, Toluca, Sinaloa, Michoacán and the State of Mexico. Soluble phenol extracts were analyzed by UV-visible spectrophotometry. The hectoliter weight (HW) and the hundred grains weight (HGW) were determined according to NMX-FF-034, while the quantification of aflatoxins was determined by enzyme immunoassay (ELISA).The hundred grains weight ranged from 18 to 51 g. The phenolic content ranged from 100 to 370 μg kg-1, the hectoliter weight from 49 to 80 kg hL-1 and the total af latoxin content from 2 to 13 μg kg-1. 25% of the corns evaluated meet the established minimum density for marketing (dough and tortillas), while the commercial corn hybrids panther, bear and DK2060, from the states of Hidalgo and Morelos, had the highest levels of aflatoxin contamination. The native corns had the highest phenolic content, implying a natural protection against storage pests.
Keywords: grain; hybrid; native; phenolic compounds; physical quality